Identifikasi Infraspesifik Fusarium oxysporum asal Subtrat Nonpisang dan Kemampuan Pindah Inangnya ke Tanaman Pisang - Gayuh Rahayu; Widodo Widodo; Ni Putu Winda Mahasari (Jurnal Fitopatologi Indonesia, 2019)
Infra-specific Identification of Fusarium oxysporum from Nonbanana Substrates and Its Ability to Move Hosts to Banana PlantsFusarium oxysporum has various life style, i.e. saprobe, endophyte and pathogen. Plant pathogenic F. oxysporum are divided into many forma specialis (f. sp.) depending on the host, for instance F. oxysporum f. sp. cubense (Foc), a causal agent of Panama disease of banana. The study aimed to determine the infraspecific identity of F. oxysporum from non-banana host and evaluate its ability to jump banana plants. Infraspecific identity was determined through a molecular approach using 3 specific primers to recognize TR4 race (TR4 F/R, TR4 F/R1, and FocSc-1/ FocSc-2), while the host’s transfer ability was tested on 2 banana cultivars namely cv. Ambon and Tanduk. Thirteen strain studied  i.e IPBCC 88,012, IPBCC 07,528, IPBCC 07,561, IPBCC 08,562, IPBCC 08,568, IPBCC 10.674, IPBCC 14.1236, IPBCC 14.1237, IPBCC 14.1238 and IPBCC 14.1239 were TR4 Foc; IPBCC 07,338 and IPBCC 14.1242 are race Foc 4. The pathogenicity test of Foc IPBCC 88,012, 07,328, 08,561, 10,674 and 14.1236 derived from cucumbers, soil, agarwood sapwood, insect nests and quinine tree endophytes showed that these strains were able to move to banana plant. This shows that Foc may not host-specific and the infaspecific term forma specialis is therefore debatable.